2001
DOI: 10.1046/j.1466-920x.2001.00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and characterizing a five‐gene cluster of ATP‐binding cassette transporters mapping to human chromosome 17q24: a new subgroup within the ABCA subfamily

Abstract: Introduction The ATP‐binding cassette (ABC) gene superfamily encodes a series of transporter proteins that move a wide variety of substances across extra‐ and intracellular membranes. Forty‐eight known human ABC genes can be divided into seven phylogenetically distinct subfamilies. The ABCA gene subfamily is found exclusively in multicellular eukaryotes. Results We report here on a unique tandem array of five ABCA genes on chromosome 17q24 defining a phylogenetically distinct group. This is the largest cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Given this observation and in accordance with the currently proposed nomenclature for human ABC transporters, the novel protein was designated ABCA9. During the preparation of this manuscript, a study came to our attention demonstrating the identification of several ABC transporters on chromosome 17q24 [25]. Among others, a cDNA was reported for ABCA9 that is largely identical with, but at the 5 0 end, 45 bp shorter than the ABCA9 mRNA reported here.…”
Section: Abca9 Cdna and Predicted Polypeptide Structurementioning
confidence: 55%
“…Given this observation and in accordance with the currently proposed nomenclature for human ABC transporters, the novel protein was designated ABCA9. During the preparation of this manuscript, a study came to our attention demonstrating the identification of several ABC transporters on chromosome 17q24 [25]. Among others, a cDNA was reported for ABCA9 that is largely identical with, but at the 5 0 end, 45 bp shorter than the ABCA9 mRNA reported here.…”
Section: Abca9 Cdna and Predicted Polypeptide Structurementioning
confidence: 55%
“…of 293 kDa making it one of the largest ABC proteins described to date. Phylogenetic analysis revealed that the known members of the ABCA subfamily can be divided into two distinct subgroups with the ABCA5, ABCA6, ABCA8, ABCA9 and ABCA10 cluster on chromosome 17 forming a distinct clade (Arnould et al, 2001;Annilo et al, 2003). ABCA12 and the newly described ABCA13 are related to each other and form an early branch off of the main cluster of ABCA genes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, with the exception of ABCA5, the five members of the cluster show a high amino acid identity (up to 78%) [4], which is not found when these genes are compared with other members of the ABCA subfamily (around 30% in most cases). This led to the subdivision of this subfamily into two distinct subgroups.…”
Section: Abca7mentioning
confidence: 92%
“…Eight members of the subfamily are located dispersedly in the genome, while ABCA5, ABCA6, ABCA8, ABCA9, and ABCA10 are arranged in a chromosome cluster on mouse chromosome 11 [2] and human chromosome 17 [4].…”
Section: Abca7mentioning
confidence: 99%
See 1 more Smart Citation